(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Plantar fasciitis is the most common cause of heel pain in adults seen in working females. Prolonged standing, running and mainly occurs due to repetitious stress causing strain to the plantar fascia. The aim of this study was to find the Frequency of plantar fasciitis and associated risk factors in working females. Objective: To determine the Frequency of plantar fasciitis and associated risk factors in working females. Methodology: Cross sectional study was conducted on 401 participants with heel pain to find out frequency and risk factors of plantar fasciitis among working females. Participants were selected from hospitals, shopping malls, beauty salons and, universities. Clinical examination through Windless test, and plantar fasciitis pain and disability scale Questionnaire and risk factors Questionnaire were recorded. Results: This study was comprised of 401 participants with mean age 1.97 ± 2.25, mean of BMI 24.27 ± 3.85. Mean ± SD of visual analogue scale and total PFPS scores were 6.50 ± 1.05 and 36.48 ± 11.05 respectively. Total population 48.8% of participants have plantar fasciitis and total population 51.1% of participants have heel pain. This study showed that 59.4% of total participants with plantar fasciitis were used to wear flat shoes, only 20.9% wear heel shoes and 19.7% wear joggers. Our result showed correlation of different variables with plantar fasciitis, included standing hours, work timings, shoe types, BMI and VAS. Significance of Standing hours showed a (p value 0.001), work timing (p value 0.001), Shoe type (0.001) and VAS (p value 0.08). However, our results did not find any significant impact of BMI (p value 0.51). Conclusion: Plantar fasciitis is found to be prevalent in working females. Standing hours, prolong working hours, shoe type and prolong standing were shown to be risk factors for plantar fasciitis.